Minimizing Waste in The Bread Production Process with The Waste Assessment Model and Failure Modes and Effect Analysis (FMEA) Method - Laturrahmi, Rizki; Fradinata, Edy; Husni , Husni (CV. Syntax Corporation Indonesia, 2025)
The achievement of production targets is a key goal for every company. To achieve these targets, it is crucial to enhance efficiency and minimize waste, such as defective products, unnecessary movements, overproduction, and excessive production time. This study aims to identify the types and amounts of waste, analyze the most dominant waste, and compare waste across three similar companies. The identification of waste was conducted using the WAM method across the three companies, revealing five major waste types with the highest percentages: Defect waste (23.489%, 21.144%, and 20.949%), Inventory waste (20.489%, 15.616%, and 18.694%), Overproduction waste (15.749%, 15.480%, and 15.391%), Waiting waste (9.382%, 12.651%, and 13.209%), and Motion waste (13.850%, 11.299%, and 10.739%). The analysis of waste causes used the Failure Mode and Effects Analysis (FMEA) method, where the highest Risk Priority Number (RPN) of 576 was associated with defective products. Recommendations to address this issue include periodic maintenance of oven machines, structured production scheduling, provision of material handling tools, and improvements in the production layout. The most dominant waste across the three companies was Defect waste, with Sarigut Bakery having the highest percentage of waste (23.489%), followed by Nafisah Bakery (21.144%) and Istana Bakery (20.949%). This study highlights the importance of addressing waste to improve production efficiency and achieve production targets.